1997
DOI: 10.1002/(sici)1098-2795(199710)48:2<251::aid-mrd13>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a protein with homology to angiotensin converting enzyme from the periacrosomal plasma membrane of equine spermatozoa

Abstract: The periacrosomal plasma membrane of spermatozoa is involved in sperm binding to oviductal epithelial cells and to the zona pellucida. A protein of 68–70 kD molecular mass was purified biochemically from the isolated periacrosomal plasma membrane of equine spermatozoa as a possible receptor for adhesion of spermatozoa to oviductal epithelial cells. A polyclonal antibody raised in rabbits against the purified equine sperm membrane protein recognized the 70 kD and an antigenically related 32 kD protein in prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 68 publications
2
14
0
Order By: Relevance
“…This raises the possibility that sperm from stst males adhere to the oviductal epithelium and͞or to secreted material in the female reproductive tract but are not efficiently released because they lack testis ACE. Consistent with this hypothesis, an ACE-related protein in equine sperm was recently localized to the periacrosomal plasma membrane (31), which is the same membrane domain that binds to the oviduct epithelium (21). It is also noteworthy in this context that testis ACE, like the somatic isozyme, appears to be membrane-bound (32,33), and a proportion of the enzyme is released during capacitation (34).…”
Section: Discussionmentioning
confidence: 74%
“…This raises the possibility that sperm from stst males adhere to the oviductal epithelium and͞or to secreted material in the female reproductive tract but are not efficiently released because they lack testis ACE. Consistent with this hypothesis, an ACE-related protein in equine sperm was recently localized to the periacrosomal plasma membrane (31), which is the same membrane domain that binds to the oviduct epithelium (21). It is also noteworthy in this context that testis ACE, like the somatic isozyme, appears to be membrane-bound (32,33), and a proportion of the enzyme is released during capacitation (34).…”
Section: Discussionmentioning
confidence: 74%
“…Our findings suggest that the sperm physiological changes may not relate to a direct role of ACE in capacitation, acrosomal reaction, or sperm-oocyte binding, because ejaculated mouse sperm may have no remaining ACE. The hypothesis that sperm ACE is not involved in postejaculatory fertilization stages is also supported by the fact that oocyte fertilization in other mammals is not altered by the presence of antibodies against this enzyme [16] or by the presence of the ACEinhibitor captopril [17,18].…”
Section: Discussionmentioning
confidence: 95%
“…A role has been suggested for ACE and angiotensin II in sperm capacitation and acrosome reaction processes [12][13][14], and the angiotensin AT1 receptor has been immunolocalized on the tail of rat and human sperm [15]. However, other results in human and domestic animals have indicated that this enzyme is not directly involved in the binding and fusion of the sperm with the oocyte [16][17][18]. We therefore extended our previous study on domestic mammals to laboratory models (mouse and rat) to determine whether germinal ACE is important for fertility within the male or female genital tract.…”
Section: Introductionmentioning
confidence: 99%
“…In sperm, mitochondrial influx of calcium through permeability transition pores may affect motility by altering the conformation of the myosin‐VI motor protein and survival (Bahloul et al, ). A study demonstrated that stallion sperm bound to oviduct epithelial cells had decreased intracellular calcium levels (Dobrinski, Ignotz, Fagnan, Yudin, & Ball, ; Dobrinski, Ignotz, Thomas, & Ball, ). Furthermore, results of this study suggested that modulation of intracellular calcium reservoir appears to be associated with viability and longevity of stallion sperm prior to fertilization.…”
Section: Introductionmentioning
confidence: 99%